Clusters and Cluster Policy in Ukraine - Pavlysh, E.V.; Poklonskyy, S.K. (Економічний вісник Донбасу, 2013)
The article deals with the cluster conception by M. Porter, its criticism by definite researchers and scientists. Special attention was paid to clustering processes in Ukraine. The existing clusters and clustering activity were analyzed. It was attempted to define existing economic clusters basing on industrial map of Ukraine analysis and available statistic data.